건강인을 대상으로 거짓침과 진짜 침을 이용한 침의 효능에 대한 연구: 위전도를 이용한 단일맹검 - 장극영; 김건일; 유준상; 고찬희; 이현숙; Jang, Keuk Young; Kim, Kun Yil; Yu, Jun Sang; Kho, Chan Hee; Lee, Hyun Sook (동의생리병리학회지, 2014)
This study aimed to prove the effects of acupuncture treatment on acupoint Joksamni(ST36) related to gastrointestinal movement. Electrogastrogram (EGG) data were obtained in 11 healthy subjects treated by real or sham needle in single-blinded condition for 40 min, including before, during acupuncture treatment, and after removing needle. According to frequency analysis of EGG, median frequency(MF) was increased by real needle in 4 subjects, MF for another 2 subjects were increased by real and sham needle and no trend shift in MF showed in other 5 subjects. Our result showed that acupuncture treatment on Joksamni has some effects on gastrointestinal movement. In this study we have applied both real acupuncture and sham acupuncture on the same subjects. So its blinding was regarded as good but was effective in about 36%~55%. Two subjects were assumed that they showed placebo effects on both real and sham acupuncture. Therefore it is necessary to perform further study on case-control and a larger number of subjects with functional dyspepsia, in order to confirm our findings.